The Effect of Gamification Marketing and E-Service Quality on Access by KAI User Satisfaction - Serli Serli; Yusuf Yusuf (International Journal Labs, 2026)
The rapid development of digital technology has transformed public transportation services through the adoption of digital applications aimed at improving user experience and satisfaction. In the railway transportation sector, the Access by KAI application serves as an important platform that provides ticketing, travel information, and other digital services. To enhance user engagement and satisfaction, gamification marketing and e-service quality have become essential strategies. Therefore, this study aims to analyze the influence of gamification marketing and e-service quality on user satisfaction with the Access by KAI application. This study employed a quantitative associative-causal approach. Data were collected through questionnaires distributed to Access by KAI users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The analysis was conducted to examine the direct effects of gamification marketing and e-service quality on user satisfaction. The results indicate that both gamification marketing and e-service quality have positive and significant effects on user satisfaction. Furthermore, the two variables jointly contribute to improving overall user satisfaction with the application. These findings suggest that engaging gamification features and high-quality electronic services are important factors in creating a positive user experience. In conclusion, the implementation of gamification strategies and continuous improvement of e-service quality play a crucial role in enhancing user satisfaction. The findings provide practical insights for transportation service providers in developing more interactive, user-oriented, and competitive digital applications.